A Conceptual Model for Anostracan Biogeography. Issue 5 (1st September 2015) - Rogers, D. Christopher
Abstract: A conceptual model for anostracan biogeography based on the "Monopolisation Hypothesis" and the "Theory of Island Biogeography" is discussed and presented. In this model anostracan species evolve allopatrically (in geographically isolated, unoccupied insular habitats), cladogenically (in small, genetically isolated founder populations via strong priority effects), or anagenically through local adaptation to changing environmental conditions. The Monopolization Hypothesis drives speciation and reverses competitive dominance patterns, leading to selection mediated priority events. Conversely, the spatial distribution of anostracan habitats (basins) drive island biogeographical patterns depending upon the relative isolation and size of any one given pool. The conceptual model presented provides a simple framework for future research in anostracan biogeography.